DO NATURAL GAS HYDRATES EXIST IN CENOMANIAN STRATA OF THE MESSOYAKHA GAS FIELD? - Ginsburg G.D.; Novozhilov A.A.; Duchkov A.D.; Prasolov E.M.; Zavarzin I.V.; Collett T.S. (My University, 2000)
The Messoyakha gas field has long been considered a world unique field where gas is extracted from natural gas hydrates. At the same time, this idea has been based solely on implicit evidence. The present study addresses the problem of the gas-hydrate-bearing capacity of the field proceeding from data on its gas production geology and temperature measurements in boreholes and from long-term (1981-97) observations of variability of gas composition. The Cenomanian productive beds of the Messoyakha field are remarkable for their inhomogeneity. Extraction of gas chiefly from the lower portion of the productive beds has caused a descending gas flow from the upper beds, which is marked by negative temperature anomalies observed during logging of abandoned wells. The conditions within the anomalies are favorable for the formation of gas hydrates related to gas extraction. Repeated analyses of PT-conditions in the field showed that they are favorable for gas formation only in the upper strata, and thus the available PT-data do not allow us to be positive about the gas-hydrate-bearing capacity of the field. We have attempted to estimate this capacity on the basis of gas geochemistry using 3000 analyses for helium, 100 analyses for hydrocarbons, carbon dioxide, and nitrogen, 23 analyses for argon, and eight analyses for all rare gases. During that work we based upon the fact that a number of gas components (primarily helium) do not form hydrates and thus should accumulate in the coexisting gas. Helium concentrations in the Messoyakha field showed to be strongly variable, which might be caused by the hydrate process, including the effects of the field operation. Data on the variability of gas composition, especially on helium concentrations, indicate that natural gas hydrates have never existed in the central part of the field (top of the anticline). Natural gases may occur (or may have occurred prior to the field operation) on the periphery of the field, whereas in its central part, in the upper portion of the productive beds, gas hydrates may have formed around the boreholes during gas extraction. We suppose that the quantitative estimation of the gas-hydrate-bearing capacity of the Messoyakha field should be the main focus of further studies.
Keywords: Cenomanian; Mesozoic::Cretaceous::Upper::Cenomanian; Мезозой::Меловая::Верхний::Сеноманский